2022
DOI: 10.20473/j.djmkg.v55.i4.p194-199
|View full text |Cite
|
Sign up to set email alerts
|

Role of cytotoxic T-lymphocyte antigen 4 (CTLA-4) expression in the pathogenesis of Warthin’s tumor growth

Abstract: Background: One of the benign salivary gland tumors is Warthin’s tumor, which is a benign tumor consisting of a papillary cystic structure covered by a double epithelial layer cells and lymphoid stroma with germinal center. Several cases have reported the Warthin’s tumor transformation into a malignant tumor such as lymphoma that develops from their stromal. Expression of cytotoxic T-lymphocyte antigen 4 (CTLA-4) as part of the immune checkpoint when highly expressed leads to a more rapid development or progre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…11,12 However, some highly expressed proteins of the immune checkpoint, such as lymphocyte-activation gene 3 (LAG-3), inhibit immune cells and indirectly support tumor growth. 13,14 Previous research conducted by Qotrunnada et al 15 showed the expression of cytotoxic T-lymphocyte antigen 4 in the solid components and germinal center lymphoid stroma of WT, which is related to T cell activity inhibition against tumor cells.…”
Section: Introductionmentioning
confidence: 97%
“…11,12 However, some highly expressed proteins of the immune checkpoint, such as lymphocyte-activation gene 3 (LAG-3), inhibit immune cells and indirectly support tumor growth. 13,14 Previous research conducted by Qotrunnada et al 15 showed the expression of cytotoxic T-lymphocyte antigen 4 in the solid components and germinal center lymphoid stroma of WT, which is related to T cell activity inhibition against tumor cells.…”
Section: Introductionmentioning
confidence: 97%